2015
DOI: 10.1007/s10067-015-3111-y
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyribonuclease I gene polymorphism and susceptibility to systemic lupus erythematosus

Abstract: The DNASE1 gene is regarded as one of the susceptible genes for systemic lupus erythematosus (SLE). Recent studies have detected the presence of a variable number of tandem repeat (VNTR) polymorphisms at intron 4 in this gene. The current study aimed to investigate the influence of current polymorphism on SLE susceptibility in a sample of the Iranian population. The study included 163 patients and 180 unrelated healthy controls. The VNTR polymorphisms in the DNASE1 gene were determined by polymerase chain reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The presence of a 56-bp variable-number tandem repeat polymorphism (VNTR) with 6 types of different repeats in intron 4 of DNASE1 in linkage disequilibrium with SNP p.Gln244Arg was revealed 45 . Among these alleles, SLE patients showed a higher distribution of allele 5 than the controls 46,47 . The fact that allele 5, together with allele 4, in the VNTR is associated with the G allele in SNP p.Gln244Arg, producing a DNase I isoform with low activity, suggests that the VNTR in DNASE1 likely confers susceptibility to SLE.…”
Section: Discussionmentioning
confidence: 92%
“…The presence of a 56-bp variable-number tandem repeat polymorphism (VNTR) with 6 types of different repeats in intron 4 of DNASE1 in linkage disequilibrium with SNP p.Gln244Arg was revealed 45 . Among these alleles, SLE patients showed a higher distribution of allele 5 than the controls 46,47 . The fact that allele 5, together with allele 4, in the VNTR is associated with the G allele in SNP p.Gln244Arg, producing a DNase I isoform with low activity, suggests that the VNTR in DNASE1 likely confers susceptibility to SLE.…”
Section: Discussionmentioning
confidence: 92%
“…Systemic lupus erythematosus (SLE) is a heterogeneous autoimmune disease characterized by pathogenic autoantibody formation against the host's nuclear antigens, immune complex deposition, and end-organ damage 1 . The exact aetiology of this disease is unknown but genetic and environmental factors have important roles in SLE pathogenesis 2 . The prevalence of this disease in women is about 8-10 times more than men and in African Americans is about 3-4 times more than Caucasian Americans 3 .…”
mentioning
confidence: 99%
“…Similarly, the involvement of DNASE1 in SLE pathogenesis in humans remains unclear. Genetic studies have identified a heterozygous non-sense mutation in DNASE1 of SLE patients (82) and single nucleotide polymorphisms (SNP) in DNASE1 that are associated with susceptibility to SLE (165,166). Nevertheless, follow up studies failed to shed light on mutations in DNASE1 in numerous cohorts of SLE patients (167-171).…”
Section: Extracellular Dnases: Key Regulators Of Cfdna-mediated Systementioning
confidence: 99%